Formation of Gender Identity of Preschoolers is an Important Aspect of Socialisation of an Individual - Kostyk, Liubov; Kostyk, Vasyl (LUMEN Publishing House, 2021)
Children'sgender perceptions are actively formed in preschool age and are an integral component of person's gender identity. The formation of sexual identity of a child continues from 2 to 7 years, and the formation of his/her imagination occurs in the process of socialization through: identification, imitation, following, modeling, direction, self-determination, encouragement, self-acceptance, self-reflection, cognitive dissonance.Child masters the social norms, patterns of behavior and cultural values of his/her nation. The gender approach to the upbringing of the preschool children should be focused on the formation and establishment of equal, gender-independent opportunities for self-realization of the individual. However as practical experience shows, the gender component and its methodological data are insufficient in terms of the content of preschool education. In preschool institutions, gender education takes place spontaneously, educators use the traditional approach to forming child's self-esteem and his stereotypes of self-perception only on the basis of gender, so it is important today to pay more attention to gender education and socialization.Experimentally it has been investigated the peculiarities of gender and age identification of the preschoolers of the preschool institution of a combined type #9 of the city of Chernivtsi. According to the research, the greater part of children of 5-6 years old are aware of their belonging to the male or female sex, having the already formed gender identity. Genderperceptions of preschool children are gender-appropriate: girls’ -feminine, and boys’ –masculine. In addition, they are stereotypical: boys have instrumental role, girls-expressive
DOI: https://doi.org/10.18662/lumproc/atee2020/15
Keywords: gende; femininity; masculinity; androgyny; gender identification